Governing ultra‐processed food and alcohol industries: the presence and role of non‐government organisations in Australia - Dori Patay; Sharon Friel; Belinda Townsend; Fran Baum; Jeff Collin; Katherine Cullerton; Katie Dain; Rodney Holmes; Jane Martin; Rob Ralston; Lucy Westerman (Elsevier, 2022)
Abstract Objective: The roles of non‐governmental organisations (NGOs) in regulating harmful commodity industries (HCIs) are understudied. The aim of this paper is to identify the NGOs and the roles that they play in the governance of the ultra‐processed food and alcohol industries in Australia. Methods: We undertook an exploratory descriptive analysis of NGOs identified from an online search based on the typology we developed of type, issue area and governance function. Results: A total of 134 relevant Australian NGOs were identified: 38 work on food issues, 61 with alcohol issues and 35 are active in both. In the food domain, 90% of NGOs engage in agenda setting, 88% in capacity building, 15% in implementation and 12% in monitoring. In the alcohol domain, 92% of NGOs are active in agenda setting, 72% in capacity building, 35% in implementation and 8% in monitoring. Conclusions: Australian NGOs are active actors in the food and alcohol governance system. Implications for public health: There are many opportunities for NGOs to regulate HCI practices, building on their relative strengths in agenda setting and capacity building, and expanding their activities in monitoring and implementation. A more detailed examination is needed of strategies that can be used by NGOs to be effective regulators in the governance system.